Effects of Intravenous and Intrathecal Dexmedetomidine in Spinal Anesthesia: A Meta‐Analysis - Niu, Xiao‐Yin (CNS Neurosci Ther, 2013)
PURPOSE: To assess the effects of dexmedetomidine on the duration of sensory and motor block, postoperative analgesia, hypotension, bradycardia, and side effects in patients undergoing spinal anesthesia. METHODS: Two researchers searched MEDLINE, EMBASE, and the Cochrane controlled trial register independently for randomized controlled trials comparing dexmedetomidine with a placebo without any language restrictions. RESULTS: A total of 412 patients from eight trials were included in this study. The results revealed that dexmedetomidine was statistically significant in prolonging the duration of sensory block (mean difference, MD = 73.55; 95% CI, [55.69, 91.40] P < 0.00001, I (2) = 89%) and motor block (MD = 59.11; 95% CI, [29.58, 88.65] P < 0.00001, I (2) = 91%) and the time to first request for postoperative analgesia (MD = 245.77, 95% CI, [143.53, 348.00] P < 0.00001, I (2) = 98%). The occurrence of hypotension (OR = 0.60, 95% CI, [0.3–1.23], P = 0.40, I (2) = 3%) and side effects (OR = 0.9, 95% CI, [0.36–2.22], P = 0.88, I (2) = 0%) was not significantly different between dexmedetomidine and placebo. However, dexmedetomidine was associated with more frequent bradycardia requiring atropine (OR = 7.55; 95% CI, [2.76–20.63], P = 0.63, I (2) = 0%). CONCLUSIONS: This meta‐analysis has shown that dexmedetomidine prolonged the duration of spinal anesthesia and improved postoperative analgesia and did not increase the incidence of hypotension and adverse events, but needs more atropine to reverse bradycardia.